Collaborating for Competency—A Model for Single Electronic Health Record Onboarding for Medical Students Rotating among Separate Health Systems - Pereira, Anne G.; Kim, Michael; Seywerd, Marcus; Nesbitt, Brooke; Pitt, Michael B.; on behalf of the Minnesota Epic101 Collaborative (Applied Clinical Informatics, 2018)
Background Use of the electronic health record (EHR) is widespread in academic medical centers, and hands-on EHR experience in medical school is essential for new residents to be able to meaningfully contribute to patient care. As system-specific EHR training is not portable across institutions—even when the same EHR platform is used—students rotating across health systems are often required to spend time away from clinical training to complete each system's, often duplicative, EHR training regardless of their competency within the EHR.Methods We aimed to create a single competency-based Epic onboarding process that would be portable across all the institutions in which our medical students complete clinical rotations. In collaboration with six health systems, we created online EHR training modules using a systematic approach to curriculum development and created an assessment within the Epic practice environment.Results All six collaborating health systems accepted successful completion of the developed assessment in lieu of standard site-specific medical student EHR training. In the pilot year, 443 students (94%) completed the modules and assessment prior to their clinical training and successfully entered clinical rotations without time consuming, often repetitive onsite training, decreasing the cumulative time as student might be expected to engage in Epic onboarding as much as 20-fold.Conclusion Medical schools with multisystem training sites with a single type of EHR can adopt this approach to minimize training burden for their learners and to allow them more time in the clinical setting with optimized access to the EHR.
Keywords: clinical informatics; professional training; education and physician; general health care providers; training and education requirements; education and strategies for health IT training; education and certification